LIPIODOL reduces the lytic activity of detergent sclerosants in vitro. (December 2021) - Gracé, Joseph; Connor, David; Bester, Lourens; Rogan, Christopher; Parsi, Kurosh
Objectives: Contrast agents are used widely in the interventional setting and in particularly in the management of vascular anomalies and have also been used in combination with sclero-embolic agents. There is limited information on the interaction of contrast agents with sclerosant agents when used as mixtures. The aim of this study was to determine the effect of mixing radiological contrast agents with detergent sclerosants and measuring the effect on change in lytic activity of detergent sclerosants in vitro and by proxy the change in potency. Methods: Red blood cell lysis was assessed following the incubation of two commonly used contrast agents, LIPIODOL® and ULTRAVIST®, mixed with detergent sclerosants, FIBROVEIN®, sodium tetradecyl sulfate (STS), and AETHOXYSKLEROL®, polidocanol (POL). Results: The density of both contrast agents was higher than STS and POL and neither of the detergent sclerosants were miscible in LIPIODOL. LIPIODOL on its own caused cell lysis (1.01%, p < 0.05) whereas ULTRAVIST did not. Fifty per cent cell lysis for sclerosant and LIPIODOL mix occurred at concentrations of: 0.041% (2.4 times greater than the control, p < 0.05) and 0.08% (3.6 times greater than the control, p = 0.06) for STS and POL, respectively. Conclusions: LIPIODOL, when mixed with sclerosant detergents (ratio 1:1) causes a reduction in the lytic activity of sclerosants and this effect was statistically significant and most prominent in lower sclerosant concentration mixtures.